PENGARUH KESIAPAN SEKOLAH TERHADAP PELAKSANAAN PROGRAM SISTEM KREDIT SEMESTER DI SMA NEGERI 9 BANDAR LAMPUNG - evi novia ikasari; Berchah Pitoewas; Yunisca Nurmalisa (FKIP Unila, 2012)
This study aimed to clarify the effect of the implementation of the school readiness program semester credit system in SMAN 9 Bandar Lampung. Theoretically, this research is useful for developing concepts of science education included into the scope of a study about the civic education of school readiness efforts in this regard include the readiness of teachers, students, infrastructure and environment for the implementation of the program semester credit system in SMAN 9 Bandar Lampung .This research method uses descriptive quantitative method with a sample 36 respondents. Basic techniques of data collection using questionnaire and analysis of data using descriptive analysis. Measurement of variables in this study is the scoring at alternative answers from questionnaires distributed to respondents. Based on the results of a study of 36 respondents obtained data on school readiness 52.8% variable, variable execution SKS 50%. As well as having tinggkat closeness of 0.62. Thus it is known that: (1) the effect of the implementation of the school readiness program semester credit system category effect, this suggests that the influence of school readiness for the implementation of the semester credit system. (2) Based on the results of testing conducted closeness effect, is known to have a strong influence on the implementation of the school readiness program semester credit system in SMAN 9 Bandar Lampung.Key word: School Readiness, Semester Credit System